2015
DOI: 10.1038/nature14182
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization of excitatory synaptic strength in primary visual cortex

Abstract: The strength of synaptic connections fundamentally determines how neurons influence each other's firing. Excitatory connection amplitudes between pairs of cortical neurons vary over two orders of magnitude, comprising only very few strong connections among many weaker ones [1][2][3][4][5][6][7][8][9] . Although this highly skewed distribution of connection strengths is observed in diverse cortical areas 1-9 , its functional significance remains unknown: it is not clear how connection strength relates to neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

79
696
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 519 publications
(783 citation statements)
references
References 39 publications
79
696
7
1
Order By: Relevance
“…To 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 our knowledge, this investigation is the first to systematically investigate the connected and unconnected pairs based on correlations (Rsc and CCG) in a microcircuit. This report further corroborates the earlier finding (Cossell et al 2015) that, high Rsc between the strongly connected neurons carries well defined and structured information in microcircuits. However, importantly, Rsc has to be calculated in optimal resolution-windows to extract meaningful information from these microcircuits.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…To 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 our knowledge, this investigation is the first to systematically investigate the connected and unconnected pairs based on correlations (Rsc and CCG) in a microcircuit. This report further corroborates the earlier finding (Cossell et al 2015) that, high Rsc between the strongly connected neurons carries well defined and structured information in microcircuits. However, importantly, Rsc has to be calculated in optimal resolution-windows to extract meaningful information from these microcircuits.…”
Section: Introductionsupporting
confidence: 92%
“…Recently, in mouse visual cortex, it has been shown that highly correlated (Rsc) neurons are strongly connected to each other (Cossell et al 2015). After computing CCGs that revealed the functional connections, we calculated Rsc for the connected and unconnected pairs in an ensemble (at a specific microcircuit) at different resolution-windows.…”
Section: High Noise Correlation Between the Functionally Connected Nementioning
confidence: 99%
See 3 more Smart Citations